A new triterpenoid from the leaves of Rhodomyrtus tomentosa (Ait.) Hassk. Issue 14 (18th July 2021) - Mo, Qinghu; Zhou, Xianli; Huang, Sixin; Zhou, Yun; Mou, Junfei; Luo, Qin; Huang, Xiao; Yang, Xinping; Chen, Xu; Liang, Chengqin
Abstract: A new triterpenoid, 2 α, 3 β, 23 α, 29-tetrahydroxyolean-11, 13 (18)-dien-28, 19 β -olide, named as rhodotomoside A (1 ), together with six known triterpenoids (2–7 ), were isolated from the leaves of Rhodomyrtus tomentosa (Ait.) Hassk by column chromatography on silica gel, reversed-phase C18 silica gel and semi-preparative HPLC. Their structures were elucidated on the basis of spectroscopic methods, including extensive 1D NMR, 2D NMR and MS spectra. The inhibition rates of α-glucosidase of compound 1 was 77.82%, and exhibited inhibitory activity against α-glucosidase with IC50 value at 0.213 ± 0.016 mg/mL. Graphical Abstract: